Implementation of an Independent Curriculum Integrated with Information and Communication Technology: A Case Study of SD Inpres Dok VIII Atas Jayapura City Papua Province - Ernawati, Ernawati; S, Neti; Wibowo, Rezky Aprilyanto (Universitas Alma Ata, 2025)
The implementation of the Merdeka Curriculum integrated with technology plays a strategic role in creating interactive, adaptive, and relevant learning experiences in line with the demands of the digital age and national education goals. However, empirical research on the application of the Merdeka Curriculum based on Information and Communication Technology (ICT) in eastern Indonesia is still limited, especially in public elementary schools such as SD Inpres Dok VIII Atas, Jayapura City, Papua Province. This study aims to examine and provide an overview of the implementation of the Merdeka Curriculum that integrates ICT in learning at the elementary school level. The method used is qualitative with a descriptive approach through literature study, observation, and interviews with teachers and students. The results of the study show that ICT integration plays an important role in the implementation of the Pancasila Student Profile Strengthening (P5) project, especially in increasing student engagement, strengthening character, and preparing them to face global challenges and digital disruption. The use of technology also supports efficient classroom management and the application of differentiated learning. However, the effectiveness of implementation is greatly influenced by school leadership support, the availability of ongoing teacher training, and access to devices and the internet. This study recommends strengthening teachers' digital capacity, equalizing ICT infrastructure, and forming learning communities. Keywords: Merdeka Curriculum, Information, and Communication Technology, Primary School.